Novel analogs of PSNCBAM-1 as allosteric modulators of cannabinoid CB1 receptor. Issue 24 (15th December 2017) - Bertini, Simone; Chicca, Andrea; Gado, Francesca; Arena, Chiara; Nieri, Daniela; Digiacomo, Maria; Saccomanni, Giuseppe; Zhao, Pingwei; Abood, Mary E.; Macchia, Marco; Gertsch, Jürg; Manera, Clementina
Graphical abstract: Abstract: In this work, we explored the molecular framework of the known CB1R allosteric modulator PSNCBAM-1 with the aim to generate new bioactive analogs and to deepen the structure-activity relationships of this type of compounds. In particular, the introduction of a NH group between the pyridine ring and the phenyl nucleus generated the amino-phenyl-urea derivativeSN15b that behaved as a positive allosteric modulator (PAM), increasing the CB1R binding affinity of the orthosteric ligand CP55, 940. The functional activity was evaluated using serum response element (SRE) assay, which assesses the CB1R-dependent activation of the MAPK/ERK signaling pathway.SN15b and the biphenyl-urea analogSC4a significantly inhibited the response produced by CP55, 940 in the low µM range, thus behaving as negative allosteric modulators (NAMs). The new derivatives presented here provide further insights about the modulation of CB1R binding and functional activity by allosteric ligands.